ENTERPRISE ARCHITECTURE: STRATEGY OF SMART VILLAGE DEVELOPMENT (VILLAGE SERVICES) USING TOGAF 9.2 - Yusriyahti, Raden Roro Hanin Ramadhan; Nur Fajrillah, Asti Amalia; Nurtrisha, Widyatasya Agustika (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2023)
Abstract: The design of Smart Village Enterprise Architecture for village government systems serves to support sustainability in facilitating the creation of Good Governance in a Village Government. One significant role in achieving Good Governance in a village is Education. Education plays a crucial role in enhancing and developing Good Governance and the SDGs values of a village. The conducted research focuses on the design of Enterprise Architecture of the Smart Village concept, with a focus on Village Services' dimension that specifically targets Education Services in a village in the Special Region of Yogyakarta. The research method utilized the TOGAF ADM 9.2 framework. The focus domain in this study includes the preliminary phase, architecture vision, business architecture, data architecture, application architecture, technology architecture, opportunities and solutions, and migration planning for the Education service in the Pagerharjo Village Government. The research result is an Enterprise Architecture blueprint as a solution to the issues that occur in the Education service in the Pagerharjo Village Government, along with an IT Roadmap as a reference for the village government in project development. It is hoped that the recommendations provided can enhance the Education services offered by the Pagerharjo village, thereby aiding the Pagerharjo Village Government in improving its score for the fourth SDGs, Quality Education. Keywords: Enterprise Architecture, Smart Village, SDGs, TOGAF ADM 9.2. Abstrak: Perancangan Enterprise Architecture Smart Village pada sistem pemerintahan Desa befungsi mendukung sustainability dalam membantu terciptanya Good Governance di suatu Pemerintahan Desa. Salah satu peranan penting terciptanya Good Governance di suatu Desa adalah Pendidikan. Pendidikan memiliki peran penting dalam peningkatan maupun pembangunan Good Governance dan nilai SDGs Desa. Penelitian yang dilakukan berfokus pada perancangan Enterprise Architecture konsep Smart Village dimensi Village Services yang berfokus pada Education Services di Desa Daerah Istimewa Yogyakarta. Metode penelitian dilakukan dengan menggunakan framework TOGAF ADM 9.2. Fokus domain yang diambil dalam penelitian ini mencakup fase preliminary phase, architecture vision, arsitektur bisnis, arsitektur data, arsitektur aplikasi, arsitektur teknologi, opportunities and solutions, dan migration planning pada layanan Pendidikan di Pemerintahan Desa Pagerharjo. Hasil dari penelitian yang dilakukan berupa blueprint Enterprise Architecture sebagai solusi dari permasalahan yang terjadi pada layanan Pendidikan di Pemerintahan Desa Pagerharjo serta IT Roadmap sebagai acuan Pemerintah Desa dalam melakukan pengembangan proyek. Diharapkan, rekomendasi yang diberikan dapat meningkatkan layanan Pendidikan yang disediakan oleh Desa Pagerharjo, sehingga mampu membantu Pemerintah Desa Pagerharjo meningkatkan score nilai SDGs ke-empat, Pendidikan yang Berkualitas. Kata kunci: Enterprise Architecture, Smart Village, SDGs, TOGAF ADM 9.2